Evaluasi Kebijakan Keahlian Ganda Guru Alih Fungsi Perhotelan di Smk Kelompok Pariwisata Jawa Tengah - Vera Ira Maya Rohi; Muhammad Sayuti; Tri Kuat; Fitri Nur Mahmudah (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to analyze government policies on dual skill transfer of teacher functions from the perspective of effectiveness, efficiency, adequacy, structuring, responsiveness, and accuracy, analyzing teacher attitudes towards teacher dual skill transfer policies. This research is a qualitative public policy and descriptive research. Data collection techniques with interviews, observation, and documentation. The respondents in this study were school principals, vocational school supervisors, Widyaiswara, PTK lecturers, heads of expertise competencies, dual skilled participant teachers, dual skilled participant companions, dual skill instructors and Hospitality and Tourism experts. Data validation using source triangulation. Data analysis techniques use qualitative data analysis techniques. The results showed that the results achieved have focused on upskilling, re-skilling, and lifelong learning for teachers, efficiently producing teachers who have competence in hospitality expertise competencies, the adequacy of the results of the dual skill program for teacher function transfer has not been fully realized. The policy strength is very high because it is the government's response to vocational education and job skills education and training with Presidential Instruction Number 9 of 2016 concerning the Revitalization of Vocational Schools. The most substantive weakness of this program is the lack of certainty of IDUKA internships and the fulfillment of the number of vocational hospitality specialization teachers who lack specialization teachers.